Venezuela and Colombia Application of a comparative education model to educommunicative development (2022)
This work aims to develop a comparative education model and apply it to the state of the art of educommunication development in Venezuela and Colombia. The categories analyzed were: the legislative framework, the works of authors related to the educommunicative theme, the institutions that develop and promote educommunication, events with educommunicative impact and teacher training related to media education.The article is based on the information gathered by two groups of researchers from both countries whose results are part of the book Media Education in Latin America. From the results obtained, three challenges for the development of educommunication are presented: the connection in the region's initiatives, the practical implementation of media education plans and the recognition of most of the States on the educommunicative development for the prevention of media impacts.